2022
DOI: 10.1097/mpg.0000000000003494
|View full text |Cite
|
Sign up to set email alerts
|

Physician and Parent Perceptions on Plant-Based Beverages as Substitutes for Cow’s Milk: A Single City Survey

Abstract: This study assessed physician and parent perceptions regarding plant-based beverage consumption in children. We surveyed 128 physicians and 215 parents of patients at University of Miami and Jackson Memorial Hospital. Among physicians, 52% recommended plant-based beverages, typically soy (33%), for cow’s milk allergy (32%). Only 40% of physicians knew the typical protein content of plant-based beverages compared to cow’s milk. Most physicians (54%) did not discuss potential health risks of plant-based beverage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…These results demonstrate the consistency between the WHO NPM and the Nutri-Score. Logically, categories with HFSS products had the highest proportions of products with a Nutri-Score of E. Surprisingly, plant-based milk, which has been found to be perceived by parents as being healthier than cow’s milk or for their children’s health [ 75 , 76 ], mainly had a Nutri-Score of E (60%) and non-compliant with the NPM (60%). The main reason is the high proportion of added sugars.…”
Section: Discussionmentioning
confidence: 99%
“…These results demonstrate the consistency between the WHO NPM and the Nutri-Score. Logically, categories with HFSS products had the highest proportions of products with a Nutri-Score of E. Surprisingly, plant-based milk, which has been found to be perceived by parents as being healthier than cow’s milk or for their children’s health [ 75 , 76 ], mainly had a Nutri-Score of E (60%) and non-compliant with the NPM (60%). The main reason is the high proportion of added sugars.…”
Section: Discussionmentioning
confidence: 99%
“…A substantial uniformity of views is derived from the reviewed literature regarding the use of plant-based formulas and plant-based drinks in the first year of life. The former are considered adequate in specific situations [ 7 , 14 , 20 , 22 , 23 , 32 , 33 , 34 , 35 , 38 , 39 , 40 , 44 , 46 ], whereas the latter’s use is suggested for the preparation of foods, once complementary feeding has begun, but not as a substitute for breast or formulated milk [ 9 , 16 , 51 , 54 , 55 , 58 , 59 , 67 , 68 , 69 , 70 ].…”
Section: Advice Common To All Choicesmentioning
confidence: 99%
“…A study based on 417 interviews showed that according to health professionals, half of consumers consider dairy products and plant-based alternatives to be nutritionally equivalent [ 33 ]. Among 215 parents who participated in an interview at the University of Miami and Jackson Memorial Hospital, 85% believed plant-based alternatives were at least equivalent to cow’s milk [ 34 ]. In another qualitative study conducted in Poland, Germany, and France, it was found that barriers and reinforcement to the consumption of plant-based alternatives depend on social factors, including health aspects, peer influences, and country-specific culinary traditions [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cow milk has long been recommended for children as it contains important nutrients such as calcium and vitamin D that are necessary for growth 1–3. However, with plant milks such as almond and oat milk becoming more widely available many parents are choosing these beverages instead of cow milk for their children 4–6. A recent Canadian study found that one-third of parents of preschool-aged children purchased plant milks 7.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] However, with plant milks such as almond and oat milk becoming more widely available many parents are choosing these beverages instead of cow milk for their children. [4][5][6] A recent Canadian study found that one-third of parents of preschool-aged children purchased plant milks. 7 With milk preferences shifting, understanding the nutritional effects of plant milk consumption in children is important.…”
Section: Introductionmentioning
confidence: 99%